Diagnostico comercial en los negocios asociados a la cámara de comercio de Latacunga clasificados dentro del sector de “Servicios Profesionales” - Lituma Galarza, Jessica Ingrid (2024)
The current research focuses on conducting a commercial análisis of professional services sector associated with Chamber Commerce of Latacunga canton, with the aim of enhancing its contribution to sustainable business development. This initiative is of particular relevance in an environment where business sustainability has become a fundamental pillar for ensuring long-term economic growth. To achieve this goal, a descriptive research methodology with a quantitative approach was employed, combining field research techniques and bibliographic review to capture the dynamics of the sector, identify trends, and assess its competitiveness. Through the application of instruments to 420 affiliated members, aspects related to the 7Ps of marketing and competitiveness were examined. The results highlight significant challenges such as lack of innovation, deficiencies in infrastructure, and regulatory barriers, thus provides a solid foundation for formulation of future strategies aimed to improve the commercial sector and, consequently, profesional offered services. In summary, this study provides a detailed and well-founded insight into the current state of the professional services sector in Latacunga canton, highlighting both its strengths and challenges, which oneserve as a fundamental starting point for designing and implementing actions that promote its sustainable development and contribution to regional economic progress.